The Effectiveness of Scratch Assisted Game-Based Discovery Learning to Improve Students’ Mathematical Problem-Solving Ability - Lukmana, Deanisa Noviana; Rohaeti, Euis Eti; Amelia, Risma (IKIP Siliwangi, 2025)
The low mathematical problem-solving ability of students in algebraic form served as the background for this research. The objectives were to describe the effectiveness of a game-based discovery learning model using the Scratch application in enhancing students' mathematical problem-solving abilities and to analyze students' challenges in implementing learning through game-based discovery learning using the Scratch application in algebraic form. The research employed a mixed methods approach with an explanatory design and a single-group pretest-posttest design. The subjects consisted of 32 Grade VII-A students from SMP Negeri 1 Batujajar. Instruments used included test questions and student response questionnaires. Data analysis techniques included prerequisite analysis and hypothesis testing. The results showed that the game-based discovery learning model using the Scratch application was effective in improving students' mathematical problem-solving abilities, with a percentage of 62.69%. This was proved through the average n-gain obtained by students, which was 0.64, and the results of the one-sample t-test on N-Gain showed a significant value at (2-tailed) = 0.000. These test results indicate that students' mathematical problem-solving abilities were in the moderate category, indicating a difference in the mean N-Gain of students' mathematical problem-solving abilities using game-based discovery learning through the Scratch application. Several challenges were identified that students faced during learning using game-based discovery learning through the Scratch application, including understanding the material, using the Scratch application itself, and fostering student cooperation throughout the learning process.